Education on Herbal Antibacterial Properties of Moringa and Moringa Tea Training - , Zehklafh Lattenni; Allloptino Latnhi (Community Service Akseprin Journal, 2024)
Bacterial infections and drug resistance constitute significant health issues in Indonesia. The general lack of awareness regarding the proper use of antibiotics is one of the main causes. Therefore, the Community Service team from the Health Analyst Study Program conducted an activity titled "Education and Dissemination of Moringa Research Results as a Herbal Antibacterial and Training on Making Moringa Tea for Villagers." This activity aims to increase public knowledge and skills about the prevention and treatment of bacterial diseases using moringa herbal medicine. The methods employed for this activity include seminars and training sessions. The seminar discussed the potential of moringa extract as an antibacterial based on the results of the team's research and its wise application. The training discusses how to make moringa tea and its benefits as an alternative treatment. Educational brochures were also distributed to the participants of the activity. The results of the activity indicated that there was an increase in public understanding of moringa as an herbal antibiotic and the wise use of antibiotics, as well as an increase in people's skills in making moringa tea. This activity is expected to have a positive impact on the health of the village community. In addition, this activity is also in line with the concept and supports the achievement of IKU (the main performance indicator of higher education) by providing an off-campus learning experience for students and involving lecturers in community service activities